The Immunobiological Agents for Treatment of Antiglomerular Basement Membrane Disease - Marina Yamashita; Mamiko Takayasu; Hiroshi Maruyama; Kouichi Hirayama (Medicina, 2023)
Combination therapy with glucocorticoids, cyclophosphamide, and plasmapheresis is recommended as the standard treatment for anti-glomerular basement membrane (anti-GBM) disease, but the prognosis of this disease remains poor. Several immunobiological agents have been administered or are expected to be useful for anti-GBM disease in light of refractory disease or the standard treatments’ tolerability. Many data regarding the use of biologic agents for anti-GBM disease have accumulated, verifying the effectiveness and potential of biologic agents as a new treatment option for anti-GBM disease. Tumor necrosis factor (TNF) inhibitors were shown to be useful in animal studies, but these agents have no clinical use and were even shown to induce anti-GBM disease in several cases. Although the efficacy of the TNF-receptor antagonist has been observed in animal models, there are no published case reports of its clinical use. There are also no published reports of animal or clinical studies of anti-B-cell-activating factor, which is a member of the TNF family of agents. Anti-interleukin (IL)-6 antibodies have been demonstrated to have no effect on or to exacerbate nephritis in animal models. Anti-C5 inhibitor was observed to be useful in a few anti-GBM disease cases. Among the several immunobiological agents, only rituximab has been demonstrated to be useful in refractory or poor-tolerance patients or small uncontrolled studies. Rituximab is usually used in combination with steroids and plasma exchange and is used primarily as an alternative to cyclophosphamide, but there is insufficient evidence regarding the efficacy of rituximab for anti-GBM disease, and thus, randomized controlled studies are required.